2004
DOI: 10.1002/ejic.200400142
|View full text |Cite
|
Sign up to set email alerts
|

Boranophosphate Salts as an Excellent Mimic of Phosphate Salts: Preparation, Characterization, and Properties

Abstract: We report on the preparation of boranophosphate salts, BPi (2), and the exploration of their properties with a view to developing a new mimic of the parent phosphate. BPi salts were easily prepared in excellent yield in a one-pot two-step reaction from tris(trimethylsilyl) phosphite, and were characterized by X-ray crystallography and IR, 1 H and 31 P NMR spectroscopy. We evaluated the acid/base character of BPi by determining its acidity constants. Likewise, we evaluated the stability of BPi at various pH val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…95 ppm typical of protonated inorganic BP i , in addition to the AMP/UMP phosphate singlet. 26 Mass spectrometric analysis (FAB negative) of the hydrolytic mixture of 3 after neutralization showed, in addition to a peak at 778.6 m/z (M + Na + + 2H + ), a peak at 423.5 m/z corresponding to ADP--B. Namely, hydrolysis does not occur symmetrically to produce two AMP/UMP molecules and one BP i . Instead, hydrolysis occurs at the P position to provide one AMP/UMP molecule and one ADP--B/UDP--B molecule.…”
Section: Synthesis Of Dinucleoside Poly(borano)phosphate Analogues 3-6mentioning
confidence: 98%
“…95 ppm typical of protonated inorganic BP i , in addition to the AMP/UMP phosphate singlet. 26 Mass spectrometric analysis (FAB negative) of the hydrolytic mixture of 3 after neutralization showed, in addition to a peak at 778.6 m/z (M + Na + + 2H + ), a peak at 423.5 m/z corresponding to ADP--B. Namely, hydrolysis does not occur symmetrically to produce two AMP/UMP molecules and one BP i . Instead, hydrolysis occurs at the P position to provide one AMP/UMP molecule and one ADP--B/UDP--B molecule.…”
Section: Synthesis Of Dinucleoside Poly(borano)phosphate Analogues 3-6mentioning
confidence: 98%
“…The borane group (−BH 3 ) is isoelectronic with oxygen in phosphate esters and also with sulfur and the methyl group present in other phosphate analogues, e.g., phosphorothioates and methylphosphonates, respectively . Despite many similarities (e.g., a tetrahedral structure, the presence of a negative charge), there are significant differences between boranephosphonates compared to phosphate diesters . The phosphorus–boron bond in boranephosphonate diesters is a dative bond formed via transfer of a lone electron pair from a phosphite diester to an electron deficient borane.…”
Section: Introductionmentioning
confidence: 99%
“…The above clarifies that due to significant bonding differences compared to phosphodiesters, incorporation of boranephosphonates into DNA or RNA can impart new properties to these biomolecules, e.g., chirality at the phosphorus centers, different bonds length, and disparate charge distribution in internucleotidic bonds. Indeed, it was found that the presence of the P-BH 3 group in oligonucleotides modulates their nuclease resistance, interaction with proteins, lipophilicity, hydrolytic stability, and secures generally low toxicity of the boron analogues. , These features constituted the basis for the development in the last two decades of boranephosphonate-modified nucleic acids as potential antisense/antigene and siRNA gene silencing agents. ,, Nucleoside boranephosphonates as phosphate analogues were introduced by Shaw, Spielvogel, and Sood in the early 1990s, and then they were further developed by Shaw, Wada, , Caruthers, and others. ,, …”
Section: Introductionmentioning
confidence: 99%
“…This small, although indicative, Δδ between H8 of A and B isomers may be explained in terms of the closer proximity to H8 of the negative charge on BH3 compared with O for the B isomer (Figure 3) and is due to the longer P-B bond (1.89 Å) compared with P–O (1.60 Å), in addition to the contribution of the B-H bond (1.25 Å). 28 Furthermore, the upfield shift of H8 of the B isomer may be due to an unconventional H-bond between the BH3 group and the relatively acidic H8 29 that is known to exist between borane-amines and acidic protons. 30 Such a preferential intramolecular H-bond results in the shielding of H8.…”
Section: Resultsmentioning
confidence: 99%